The Legislature in the Nerves of Socio-Economic Governance and Development: The Nigerian National Assembly in Perspective - Ayodele, Bonnie Ayodele; Akanmu, Kolawole Ismaila Akanmu (African Journal of Stability and Development (AJSD), 2024)
In modern democracies, government is typically structured around the tripod of the legislative, executive, and judicial arms. However, a common misconception exists that, among these three arms, only the executive significantly contributes to a nation's socio-economic development. This misconception is particularly prevalent in Nigeria, where awareness of the substantial contributions made by the legislative arm is lacking. This study reveals that the National Assembly of Nigeria, endowed with numerous powers and functions as stipulated by the constitution, plays a crucial role in the nerves of the nation's socio-economic development. These powers encompass law-making, representation, oversight, and constituency services. An evaluation of the National Assembly's roles, specifically its constitutionally assigned roles, indicates substantial contributions to the nation's socio-economic development. The findings underscore the National Assembly's impactful initiatives, such as combating corruption through establishing commissions like the Economic and Financial Crimes Commission (EFCC) and the Independent Corrupt Practices and Other Related Offenses Commission (ICPC). Additionally, efforts in rehabilitating regions affected by militant groups and terrorists, achieved through commissions like the Niger Delta Development Commission (NDDC) and the Northeast Development Commission (NEDC), are evidence of its developmental strides. The National Assembly's legislative acts have also positively changed the educational sector and electoral system. The study acknowledges the National Assembly's commendable role in addressing and managing diversities and its active involvement in various constituency services. However, it identifies impediments that hinder optimal performance, including executive dominance, disconnection from society, inadequate laws supporting institutional functions, lack of political will, and insufficient training for legislators and supporting staff. Recognising these challenges as surmountable, the study proposes an agenda for reforming its institutional responsibilities. Recommendations include strengthening relevant laws to fortify the institution, encouraging legislators to develop the political will necessary for effective oversight, implementing comprehensive training and re-training programmes for legislators and support staff, and minimising legislators' turnover to capitalise on accumulated experiences. The study concludes with the belief that addressing these constraints will pave the way for enhanced performances by the National Assembly, ultimately contributing to the overall betterment of the country.